The importance of Sign Language qualification for quality Nursing care for deaf patients (Research, Society and Development, 2025)
This study aims to discuss the importance of Brazilian Sign Language (Libras) in promoting accessibility in healthcare. The inclusion of people with disabilities in various social spaces is ensured by Brazilian legislation, which seeks to guarantee equal opportunities and access to essential services. Although palliative strategies exist, such as lip reading, gestures, mime, writing, assistive technologies, or the presence of interpreters, these alternatives do not replace direct communication through Libras. The continuous training of healthcare professionals in Libras is fundamental, since the subject is not mandatory in undergraduate health courses—especially in Nursing. This study is based on bibliographic research, grounded in scientific articles published in the last decade, legislation and guidelines related to accessibility and the rights of the deaf population in the context of healthcare, as well as research addressing the inclusion of Libras in the training of nursing professionals.